2013
DOI: 10.1017/s1461145713000990
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neonatal NOS-1 inhibitor exposure on neurobehavioural measures and prefrontal-temporolimbic integration in the rat nucleus accumbens

Abstract: Nitric oxide (NO) is a gaseous neurotransmitter that plays a significant role in the establishment and refinement of functional neural circuits. Genetic and post-mortem studies have suggested that neuronal NO synthase (NOS-1) activity may be compromised in frontal and temporal lobes, and related structures, in schizophrenia. The goal of this study was to determine if there is a link between neonatal disruptions in NO signalling and disturbances in the development and function of prefrontal-temporolimbic circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Considering the long‐term preventive effect of SNP, it should also be taken into account that a disruption in nitric oxide signaling has been associated with long‐term behavioral and neuroanatomical abnormalities that might be associated with schizophrenia—see . The maturation of neurons and synaptogenesis are modulated by NO.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the long‐term preventive effect of SNP, it should also be taken into account that a disruption in nitric oxide signaling has been associated with long‐term behavioral and neuroanatomical abnormalities that might be associated with schizophrenia—see . The maturation of neurons and synaptogenesis are modulated by NO.…”
Section: Discussionmentioning
confidence: 99%
“…Improper migration of NADPH‐d, a nitric oxide synthase, neurons might lead to a disturbance in the nitrergic transmission interfering with the neurodevelopmental process culminating with the manifestation of schizophrenia later in life . In this sense, neonatal nitric oxide synthase inhibition leads to an increase in dopamine agonists‐ and stress‐induced hyperlocomotion as well as deficits in social interaction, prepulse inhibition of startle, latent inhibition, and short‐term recognition memory . In this respect, the hypertension of the SHR strain has been associated, among other factors, to a decrease of nitric oxide availability due to an increase in peripheral free radicals .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decreased synthesis of nitric oxide in the brain is also discussed as a pathogenic factor of mental disorders. It has been shown that nNOS deficiency in experiments results in cognitive and behavioral disturbances, pathognomonic for schizophrenia (Kirchner et al, 2004 ; Dec et al, 2014 ). Therefore, even the migration of neurons described above may result in NO deficit in some areas and in cognitive deficiency.…”
Section: Nitric Oxide In Pathogenesis Of Schizophreniamentioning
confidence: 99%